Conservation and divergence of methylation patterning in plants and animals - Feng, Suhua; Cokus, Shawn J; Zhang, Xiaoyu; Chen, Pao-Yang; Bostick, Magnolia; Goll, Mary G; Hetzel, Jonathan; Jain, Jayati; Strauss, Steven H; Halpern, Marnie E; Ukomadu, Chinweike; Sadler, Kirsten C; et al. (Proceedings of the National Academy of Sciences - PNAS, 2010)
Cytosine DNA methylation is a heritable epigenetic mark present in many eukaryotic organisms. Although DNA methylation likely has a conserved role in gene silencing, the levels and patterns of DNA methylation appear to vary drastically among different organisms. Here we used shotgun genomic bisulfite sequencing (BS-Seq) to compare DNA methylation in eight diverse plant and animal genomes. We found that patterns of methylation are very similar in flowering plants with methylated cytosines detected in all sequence contexts, whereas CG methylation predominates in animals. Vertebrates have methylation throughout the genome except for CpG islands. Gene body methylation is conserved with clear preference for exons in most organisms. Furthermore, genes appear to be the major target of methylation in Ciona and honey bee. Among the eight organisms, the green alga Chlamydomonas has the most unusual pattern of methylation, having non-CG methylation enriched in exons of genes rather than in repeats and transposons. In addition, the Dnmt1 cofactor Uhrf1 has a conserved function in maintaining CG methylation in both transposons and gene bodies in the mouse, Arabidopsis, and zebrafish genomes.